Atlas of the immune cell repertoire in mouse atherosclerosis defined by single-cell RNA-sequencing and mass cytometry - Winkels, Holger; Ehinger, Erik; Vassallo, Melanie; Buscher, Konrad; Dinh, Huy Q.; Kobiyama, Kouji; Hamers, Anouk A. J.; Cochain, Clement; Vafadarnejad, Ehsan; Saliba, Antoine-Emmanuel; Zernecke, Alma; Pramod, Akula Bala; et al. (Circulation Research, 2018)
Rationale: Atherosclerosis is a chronic inflammatory disease that is driven by the interplay of pro- and anti-inflammatory leukocytes in the aorta. Yet, the phenotypic and transcriptional diversity of aortic leukocytes is poorly understood. Objective: We characterized leukocytes from healthy and atherosclerotic mouse aortas in-depth by single-cell RNAsequencing and mass cytometry (cytometry by time of flight) to define an atlas of the immune cell landscape in atherosclerosis. Methods and Results: Using single-cell RNA-sequencing of aortic leukocytes from chow diet- and Western diet-fed Apoe- and Ldlr- mice, we detected 11 principal leukocyte clusters with distinct phenotypic and spatial characteristics while the cellular repertoire in healthy aortas was less diverse. Gene set enrichment analysis on the single-cell level established that multiple pathways, such as for lipid metabolism, proliferation, and cytokine secretion, were confined to particular leukocyte clusters. Leukocyte populations were differentially regulated in atherosclerotic Apoe- and Ldlr- mice. We confirmed the phenotypic diversity of these clusters with a novel mass cytometry 35-marker panel with metal-labeled antibodies and conventional flow cytometry. Cell populations retrieved by these protein-based approaches were highly correlated to transcriptionally defined clusters. In an integrated screening strategy of single-cell RNA-sequencing, mass cytometry, and fluorescence-activated cell sorting, we detected 3 principal B-cell subsets with alterations in surface markers, functional pathways, and in vitro cytokine secretion. Leukocyte cluster gene signatures revealed leukocyte frequencies in 126 human plaques by a genetic deconvolution strategy. This approach revealed that human carotid plaques and microdissected mouse plaques were mostly populated by macrophages, T-cells, and monocytes. In addition, the frequency of genetically defined leukocyte populations in carotid plaques predicted cardiovascular events in patients. Conclusions: The definition of leukocyte diversity by high-dimensional analyses enables a fine-grained analysis of aortic leukocyte subsets, reveals new immunologic mechanisms and cell-type-specific pathways, and establishes a functional relevance for lesional leukocytes in human atherosclerosis.
CRIS-Team Scopus Importer:2023-03-23
Keywords: atherosclerosis; flow cytometry; immune system; leukocytes; lymphocytes; macrophages; mass cytometry; single-cell RNA-sequencing